Combination of presurgical nasoalveolar moulding and nasal stent for correction of nose contractures: Kombinasi presurgical naso alveolar moulding dan nasal stent untuk koreksi hidung yang kontraktur - Warni; Machmud, Edy; Jubhari, Eri Hendra; Aziz, Astri Al Hutami (Makassar Dental Journal PDGI Makassar, 2025)
Cleft lip and palate (CLP) is a common congenital defect of the craniofacial region. Presurgical nasoalveolar moulding (PNAM), which reshapes the alveolar and nasal segments before surgical repair, is an orthopaedic plate that can passively reposition the alveolar segment and nasal cartilage before surgical repair. PNAM with nasal stent has the advantages of correcting immature nasal cartilages and maintaining a normal position. This article describes the stages and results of pre-surgical treatment of an infant with PNAM with a single nasal stent of a complete unilateral CLP infant sinistra. A 7-day-old male infant with unilateral complete labiognatopalatoschizis sinistra was treated using a PNAM nasal stent design to form nasal cartilage. The premaxilla-ry position was corrected by making periodic adjustments to the anatomical surface of the PNAM. The gap was narrowed so that the premaxillary position was improved, and the nasal morphology was more symmetrical between the cleft and non-cleft sides. It is concluded that pre-surgical treatment with PNAM creation with a single nasal stent in complete unilateral CLP infants can correct the premaxillary position and narrow the gap before labioplasty.